2010
DOI: 10.1111/j.1551-2916.2009.03573.x
|View full text |Cite
|
Sign up to set email alerts
|

Temperature‐Insensitive Large Strain of (Bi1/2Na1/2)TiO3–(Bi1/2K1/2)TiO3–(K0.5Na0.5)NbO3 Lead‐Free Piezoceramics

Abstract: BNT-BKT) lead-free piezoceramics was investigated. Polarization and strain hysteresis loops indicate that the ferroelectric order is disrupted significantly with the addition of KNN as a replacement for BNT and the destabilization of the ferroelectric order is accompanied by an enhancement of the unipolar strain, which peaks at a value of B0.48% (corresponding to a large signal d 33 of B600 pm/V) at 1 mol% KNN content. This strain was analyzed as derived from an electrostrictive effect at lower electric fields… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

19
66
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 225 publications
(88 citation statements)
references
References 25 publications
(37 reference statements)
19
66
3
Order By: Relevance
“…This can be evident from the fact that the NBT–BT films have a much better linearity in strain− E -field curve compared to that of bulk: the film shows linear relation during E -field unloading (see, Fig. 3), whereas the bulk exhibits quadratical relation during both the E -field loading and unloading 19,53 . The variation of the linearity can also be recognized in the PMN−PT with different PT content 42 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…This can be evident from the fact that the NBT–BT films have a much better linearity in strain− E -field curve compared to that of bulk: the film shows linear relation during E -field unloading (see, Fig. 3), whereas the bulk exhibits quadratical relation during both the E -field loading and unloading 19,53 . The variation of the linearity can also be recognized in the PMN−PT with different PT content 42 .…”
Section: Resultsmentioning
confidence: 96%
“…The PMN−PT is known as a prototypical relaxor ferroelectrics predominantly exhibiting electrostrictive nature. The NBT-based materials including NBT–BT likewise show electrostriction and relaxor behavior especially below the E -field where the phase transition occurs 19,51,53 but differently from the PMN−PT, having anti-ferro/ferri-ferro-electric ordered nanodomains derived from the P4bm phase 15 . On the other hand, as for the present NBT–BT film, the sputtering-derived stress and internal bias field give rise to enhanced polarization leading to the ferroelectric ordering, so that the contribution from electrostriction would become less.…”
Section: Resultsmentioning
confidence: 99%
“…Bi 0.5 Na 0.5 TiO 3 (BNT) based ceramics produced in solid solution with (among others) either BaTiO 3 (BT)5, Bi 0.5 K 0.5 TiO 3 (BKT)6, K 0.5 Na 0.5 NbO 3 (KNN)7 or combinations thereof8910111213 have been shown to possess usable electric-field-induced strains of the order of 0.4%14. For given compositions, an initial pseudo-cubic non-ferroic structure has been observed to transform to a ferroic state with majority tetragonal15, or a phase mixture of tetragonal and rhombohedral symmetries16.…”
mentioning
confidence: 99%
“…That said, recent work by Rödel on a chemically similar solid solution based on Bi(Zn 1/2 Ti 1/2 )O 3 has many similar features to the present work. 20,22 Interestingly, using in-situ diffraction techniques, there was no evidence of a phase transition under an electric field. 22 One important factor that must be considered is that preliminary electron microscopy investigations have revealed that the complex solid solutions in this study exhibit a highly inhomogeneous microstructure.…”
mentioning
confidence: 99%